Banking Management System – Core 2 (Communication Management, Savings Tracking, Social Performance Monitoring, Consolidation): Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This project aims to meet the Bachelor of Science in Information Technology requirements. The Core II Banking Transaction Management System aims to provide a secure way to manage customer information, fostering strong relationships between banks and their customers. Our system offers multi-level confidentiality solutions to increase customer satisfaction and facilitate communication between the bank and the client.  Our system has five sub-modules: Savings Tracking, Consolidation, Communication Management, Cash Transaction, and Social Performance Monitoring. The researchers identified data theft and unstructured information as challenging issues to tackle. Therefore, the proponents developed a system that enhances the quality and efficiency of services, enables faster transaction processes, and allows authorized users to access files and other transactions conveniently, all while maintaining authentication and protection.  This paper discusses the comparative study of agile processes. Agile techniques are useful in software project management, software schedule management, and other domains. Agile procedures aim to satisfy the client by reducing development timeframes and defect rates. The agile process follows the software development life cycle, which includes requirements gathering, analysis, design, coding, testing, delivering partially implemented software, and waiting for client feedback. Customer satisfaction is our highest priority throughout the process, with faster development time.  Our framework for software development, known as the software development life cycle (SDLC), outlines the tasks to be completed at each stage of the process. This includes planning, analysis, design, coding, testing, and maintenance, all of which are tailored to meet the specific requirements of our customers. The choice of development model is dependent on the application in question. The agile process is a software development approach that emphasizes customer satisfaction as the highest priority. This iterative process allows for direct evaluation of the software by the customer.